Diseño de cuentos infantiles con ilustraciones digitales para el aprendizaje de los mitos religiosos de Chimborazo - Espin Pozo, Jairo Manuel (2018)
The insertion of technology in all social areas takes place in the loss of oral tradition, in addition to acculturation, with elements imposed mainly by the USA. Children and young people are unaware of the myths, legends and traditions of the province of Chimborazo. Another cause is the shortage of illustrated products, publishing house that encourage the habit of reading in this target audience. The illustrations are a graphic resource of child preference, so they get their attention by encouraging the target to research graphic, (illustrated book). The proposal uses resource quality illustrations to have children’s illustrations were analyzed: theories, preferences, characteristics and processes, related to the target. In addition, it was inquired bibliographical information and oral tradition from the ten myth-religious histories of the cantons that belong to the province of Chimborazo. The research used the ethnographic method to define the textual environment and Scott's design method for graphic development. The final proposal presents the dynamic form, the main and secondary characters that were designed in a caricatured way after the readers. In addition, it presents a semiotic richness in the scenarios and constructive and scenographic details. It will contribute to strengthen the oral tradition, as long as the users give it a good use.